Edukasi Adab Membaca Qur'an sebagai Seorang Penghafal di Rumah Tahfidz Al-Hasan Pawon Tlogo menggunakan Media 2D Scene Animation - Sulaiman Sulaiman; Rahmah Rahmah; Aunur Rafik; Mitra Yadiannur; Fatinatush Shalihah; Rahma Pitria Ningsih (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community engagement initiative aimed to enhance students’ understanding of proper etiquette in reciting the Qur’an through the use of 2D animated educational media. Conducted at Rumah Tahfidz Al-Hasan Pawon Tlogo, the activity involved 30 young Qur’an memorizers from various age groups, accompanied by educators and foundation representatives. The combination of visual storytelling and interactive discussion proved effective in fostering active participation and improving comprehension of the moral values conveyed. Key success factors included the alignment of media with the participants’ cognitive profiles, the supportive role of facilitators, and the conducive learning environment. The outcomes indicate that animation-based instruction not only facilitates the internalization of Qur’anic etiquette but also cultivates a joyful and meaningful learning experience. This program exemplifies the synergy between higher education institutions and religious learning centers in promoting contextual and applicable Qur’anic literacy.